2022
DOI: 10.1111/jsr.13548
|View full text |Cite
|
Sign up to set email alerts
|

No perfect sleep! A systematic review of the link between multidimensional perfectionism and sleep disturbance

Abstract: Summary The view that perfectionists are prone to experiencing sleep disturbance is widely held. Yet, almost three decades of empirical research have yielded conflicting results. Whereas some researchers viewed perfectionism as a risk factor for sleep disturbance, others spoke of “adaptive” or “positive” forms of perfectionism in the context of sleep. The multidimensional conceptualisation of perfectionism may resolve this disagreement. Thus, this systematic review aimed to clarify the perfectionism‒sleep dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 144 publications
0
4
0
1
Order By: Relevance
“…Against this background, we focused on SOP and SPP as two specific dimensions of perfectionism in the present study. 1 Perfectionistic concerns have consistently been related to a variety of sleep problems, whereas perfectionistic strivings have been mostly unrelated to sleep quality in previous research (see Molnar et al, 2020;Stricker et al, 2022, for reviews on perfectionism and sleep). To date, two studies have investigated and confirmed these findings in samples of employees (Flaxman et al, 2018;Reis & Prestele, 2020).…”
Section: Multidimensional Perfectionism and Differences In Sleep Qualitymentioning
confidence: 95%
See 2 more Smart Citations
“…Against this background, we focused on SOP and SPP as two specific dimensions of perfectionism in the present study. 1 Perfectionistic concerns have consistently been related to a variety of sleep problems, whereas perfectionistic strivings have been mostly unrelated to sleep quality in previous research (see Molnar et al, 2020;Stricker et al, 2022, for reviews on perfectionism and sleep). To date, two studies have investigated and confirmed these findings in samples of employees (Flaxman et al, 2018;Reis & Prestele, 2020).…”
Section: Multidimensional Perfectionism and Differences In Sleep Qualitymentioning
confidence: 95%
“…Specifically, in a sample of adults, Molnar et al (2020) found a positive indirect effect of SOP on both sleep efficiency and quality via lower levels of perceived stress, whereas they found the opposite pattern for SPP. However, Stricker et al (2022) recently concluded in their review that little convincing evidence exists to support the adaptiveness of SOP concerning sleep. These findings point toward a need for gaining more knowledge of the different mechanisms.…”
Section: Multidimensional Perfectionism and Differences In Sleep Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Порушення сну у фармацевтичних фахівців (ФФ) тісно пов'язані з низкою захворювань, які належать до професійних та сьогодні поглиблюються факторами, що зумовлені воєнним станом, тривалою пандемією COVID-19, бурхливим розвитком інформаційних технологій, несприятливою соціальною ситуацією, які додають нервового напруження на роботі [7][8][9][10].…”
unclassified
“…Stricker et al (2022) provide us with a systematic review of the relationships between perfectionism, measured multidimensionally, and sleep disturbances. This non‐meta‐analytic approach resulted in 24 relevant empirical studies, and it seems that concerning perfectionism, perfectionistic concerns were robustly linked to sleep disturbance.…”
mentioning
confidence: 99%